2018
DOI: 10.1101/432260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-parasite interaction explains variation in prevalence of avian haemosporidians at the community level

Abstract: 15 2 16 ABSTRACT17 Parasites are a selective force that shape host community structure and dynamics, but 18 host communities can also influence parasitism. Understanding the dual nature from 19 host-parasite interactions can be facilitated by quantifying the variation in parasite 20 prevalence (i.e. the proportion of infected host individuals in a population) among host 21 species and then comparing that variation to other ecological factors that are known to 22 also shape host communities. Avian haemosporidia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…In the present study, a relatively low level of haemosporidian infection was found among 36 species which are strongly related to habitat characteristics influence parasite transmission. These factors comprised scarcity of insect vectors, resistance to parasite, sampling time, host and immune system, habitat characterization such as temperature, elevation, and rain-fall and host specifity of parasite ( Bensch et al, 2012 ; Garcia-Longoria et al, 2019 ; Gutierrez-Lopez et al, 2015 ; Rivero de Aguilar et al, 2018 ; Soares et al, 2016 ). Blood collection of migratory birds and some raptors are performed in fall and winter, and low prevalence of haemosporidian parasites may be influenced by seasonal and sampling parameters when suitable vectors are absent.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a relatively low level of haemosporidian infection was found among 36 species which are strongly related to habitat characteristics influence parasite transmission. These factors comprised scarcity of insect vectors, resistance to parasite, sampling time, host and immune system, habitat characterization such as temperature, elevation, and rain-fall and host specifity of parasite ( Bensch et al, 2012 ; Garcia-Longoria et al, 2019 ; Gutierrez-Lopez et al, 2015 ; Rivero de Aguilar et al, 2018 ; Soares et al, 2016 ). Blood collection of migratory birds and some raptors are performed in fall and winter, and low prevalence of haemosporidian parasites may be influenced by seasonal and sampling parameters when suitable vectors are absent.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the number of lineages most often does not add up to the number of infected birds. Loiseau et al 2010;Rifkin et al 2012;Garcia-Longoria et al 2014;Olsson-Pons et al 2015), as well as detection biases, i.e. abortive stages of development and PCR bias.…”
Section: Host Preferencesmentioning
confidence: 99%
“…Thus, the specific associations we identified could be either seen as a result of an ongoing infection, or indirectly causative by influencing host attractiveness to vectors. Other factors that determine whether birds become infected with malaria can be for example host genetics (Sepil et al 2013), age (van Oers et al 2010), sex (Calero‐Riestra and García 2016), vector abundance (Okanga et al 2013), habitat characteristics (Ferraguti et al 2018), and interactions between parasite lineage and host species (Garcia‐Longoria et al 2019).…”
Section: Discussionmentioning
confidence: 99%